Recovery from high-intensity training sessions in female soccer players - Sjökvist, J.; Laurent, M. C.; Richardson, M.; Curtner-Smith, M.; Holmberg, H. C.; Bishop, P. A. (The Journal of Strength and Conditioning Research, 2011)
This study quantified the performance recovery time requirements after training sessions using high-intensity soccer drills with and without the ball in National Collegiate Athletic Association Division I female soccer players. Recovery time periods (24, 48, 72 hours of rest) from high-intensity soccer training sessions using drills with and without the ball were evaluated. Markers of recovery were each individual's performance relative to baseline performance in countermovement jump (CMJ) height, 5 bound jumps for distance (5BT), 20-m sprint (20SP), session rating of perceived effort (S-RPE), and heart rate (HR). Repeated-measures analysis of variance revealed a significant difference in CMJ performance (p < 0.04) and S-RPE (p < 0.02) after 24 hours of rest but not at 48 or 72 hours compared to baseline. There were no significant differences in 20SP, 5BT, or HR after 24, 48, or 72-hour recovery (p > 0.05). Therefore, high-intensity training drills produced a sufficient conditioning stimulus with little chance of underrecovery for the performance measures we tested. Countermovement jump and S-RPE may be more sensitive performance recovery indicators.